To solve the equation we will apply the distributive property by multiplying 17/3 by each term in the parentheses:
17/3(x) - 17/3(3/2) = -5/4
This simplifies to:
17/3x - 51/6 = -5/4
Now we will simplify the fractions:
x(17/3) - 17/2 = -5/4
Next, we need to find a common denominator for both fractions:
x(17/3) - (17/2)(2/2) = -5/4
This simplifies to:
17x/3 - 34/4 = -5/4
Now, let's combine the fractions:
17x/3 - 17/2 = -5/4
To further simplify, let's find a common denominator for the fractions:
17x/3 - (17/2)(3/3) = -5/4
This simplifies to:
17x/3 - 51/6 = -5/4
Now, we can add 51/6 to both sides to isolate the x term:
17x/3 = -5/4 + 51/6
To find a common denominator for the fractions:
17x/3 = -15/12 + 102/12
This simplifies to:
17x/3 = 87/12
Now, we can multiply both sides by 3 to cancel out the fraction on the left side:
17x = 87/12 * 3
Next, let's simplify the fraction on the right side:
17x = 261/12
Now, divide both sides by 17 to solve for x:
x = (261/12) / 17
Finally, we can simplify the fraction on the right side:
x = 261/12 รท 17
x = 15.3529
Therefore, the solution to the equation is x = 15.3529.
Solve the following equation using the distributive property
17/3(x-3/2)=-5/4
1 answer